Lymphoid architecture - the meeting places that spark the body’s immune reactivity: design and dynamics 1 - Hunt, Simon (Henry Stewart Talks, 2021)
Primary and secondary immunological responses, Secondary lymphoid organs and their connectivity via lymphatic vessels, Lymph nodes structure and function, Lymphocytes